Ranking in Canadian Gastroenterology Residency Match: What Do Residents and Program Directors Want? - Khurram J Khan; Mark A Levstik (Canadian Journal of Gastroenterology)
BACKGROUND: Matching to a gastroenterology (GI) fellowship position in Canada is increasingly competitive.